Energy Efficiency in Large Scale Distributed Systems COST IC0804 European Conference, EE-LSDS 2013, Vienna, Austria, April 22-24, 2013, Revised Selected Papers - Pierson, Jean-Marc.; Da Costa, Georges; Dittmann, Lars.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes revised selected papers from the Conference on Energy Efficiency in Large Scale Distributed Systems, EE-LSDS, held in Vienna, Austria, in April 2013. It served as the final event of the COST Action IC0804 which started in May 2009. The 15 full papers presented in this volume were carefully reviewed and selected from 31 contributions. In addition, 7 short papers and 3 demo papers are included in this book. The papers are organized in sections named: modeling and monitoring of power consumption; distributed, mobile and cloud computing; HPC computing; wired and wireless networking; and standardization issues.
Modeling and monitoring of power consumption -- Solving some Mysteries in Power Monitoring of Servers: Take Care of your Wattmeters! -- Energy Box: A Trace-driven Tool for Data Transmission Energy Consumption Studies -- Myths in PMC-based Power Estimation -- Energy Consumption Library -- Monitoring and Management Platforms for IT and Home Appliances -- Modelling Power Adaption Flexibility of Data Centres for Demand-Response Management -- Stress Cloud: An Infrastructure stresser for Virtual Machine Managers -- An Intelligent and Adaptive Threshold-Based Schema for Energy and Performance Efficient Dynamic VMs Consolidation Energy Characterization of Data Mining Algorithms on Mobile Devices -- Snooze: an Autonomic and Energy-Efficient Management System for Private Clouds -- DCworms - a tool for simulation of energy efficiency in data centers -- Energy Efficiency in Secure and Dynamic Cloud Storage -- A Holistic Model of the Performance and the Energy-Efficiency of Classical Hypervisors in an HPC Environment -- Runtime Scheduling of the LU Factorization: Performance and Energy -- A Three Step Blind Approach for Improving HPC Systems' Energy Performance -- Performance Evaluation and Energy Efficiency of High-Density HPC Platforms Based on Intel, AMD and ARM Processors -- Enhancing IEEE 802.11 Energy Efficiency for Continuous Media Applications -- Real-World Energy Measurements of a Wireless Mesh Network -- An Evolutionary Algorithm Based Dynamic Energy Management Framework for IP over DWDM Core Network -- Autonomic computing to manage green Core networks with Quality of Service -- Large Scale Analysis of BitTorrent Proxy for Green Internet File Sharing -- Energy Efficiency Issues in Information-Centric Networking -- Cutting Down the Energy Cost of Geographically Distributed Cloud Data Centers -- Green IT for Standardization Bodies, Initiatives and their relation to Green IT focused on the Data Centre Side -- Towards Service Orchestration between Smart Grids and Telecom Networks.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Operating systems (Computers).; Database management; Electric engineering; Computer Science; Database Management; Computer Communication Networks; Energy Technology; System Performance and Evaluation; Operating Systems